Safety Study of Combination Treatment: Deep Brain Stimulation and Transcranial Magnetic Stimulation - Magsood, Hamzah; Syeda, Farheen; Holloway, Kathryn; Carmona, Ivan C.; Hadimani, Ravi L. (Frontiers in Human Neuroscience, 2020)
Patients with advanced Parkinson’s disease often receive deep brain stimulation treatment, in which conductive leads are surgically implanted in the brain. While DBS treats tremor and rigidity, patients often continue to suffer from speech and swallowing impairments. There is preliminary evidence that transcranial magnetic stimulation of the cortex may be beneficial for these symptoms. However, the potential electromagnetic interactions of the strong magnetic fields from TMS on the conductive leads is unknown, and the combination therapy has not been approved for use. In this paper, we report experimental study of the safety of combining DBS and TMS. We fabricated an anatomically accurate head and brain phantom with electrical conductivities matching cerebrospinal fluid and averaged conductivity of grey and white matter. Induced current on an implanted DBS probe in the brain phantom was measured. Our results show that transcranial magnetic stimulation will induce current values in the range or higher than typical DBS stimulation current. Thus, the combination of TMS/DBS treatment might cause over-stimulation in the brain when stimulated with 100% TMS current intensity.